Analisis Pemahaman Sertifikasi Halal pada Usaha Mikro Kecil dan Menengah (UMKM): Studi Kasus di Kampung Ceungceum Kecamatan Leuwisari Kabupaten Tasikmalaya - Aisyah, Dara Istia; Nurmalia, Fidhya; Athiyyah Nur Azizah, Nisrina; Marlina, Lina (Journal of Islamic Economics Studies and Practices, 2023)
This research aims to analyze the understanding of halal certification in micro, small and medium enterprises (MSMEs). This research was conducted using a qualitative descriptive approach. Data collection was carried out using observation, interviews and documentation techniques from related sources. Respondents totaled 15 MSMEs by distributing questionnaires directly. Of the total number of respondents, 33.3% or 5 people understood halal certification and 66.7% or 10 people still did not understand. The research results show that understanding of halal certification in Ceungceum Village is still relatively low due to a lack of outreach activities. The government's role is needed to increase understanding of MSMEs by holding outreach and mentoring activities to make it easier to obtain halal certification in villages.